+0  
 
0
32
1
avatar

Let f(x)=3x^2  - 4x - x^2 + 7x + 8. Find the constant k such that f(x)=f(k-x) for all real numbers x. 

 Feb 12, 2021
 #1
avatar+116125 
+1

3x^2    -4x   -x^2  + 7x  +  8  simplifies  to

 

2x^2  +  3x  +  8  =   f(k -x)

 

So

 

2x^2  +  3x  +  8   =   2(k - x)^2  + 3(k -x)  +  8

 

2x^2  + 3x +  8 =  2 ( k^2  - 2kx + x^2)  + 3k  -3x   +  8

 

2x^2  +  3x   =  2k^2  - 4kx  + 2x^2  + 3k  - 3x

 

2k^2  -4kx  + 3k   -6x=  0

 

2k  ( k - 2x)  +  3 ( k  - 2x)   = 0

 

(2k + 3)  ( k  - 2x)  =  0     the  first factor  set = to   0   will give us what we need

 

2k  +  3   = 0

 

2k   =  -3

 

k = -3/2

 

 

cool cool cool

 Feb 12, 2021

36 Online Users

avatar
avatar
avatar
avatar